ANALISIS BENTUK KALIMAT TIDAK EFEKTIF DALAM TEKS BERITA BERBAHASA JAWA KARYA SISWA KELAS VIII SMP NEGERI 2 SURAKARTA TAHUN AJARAN 2017/2018 - Sari, Neno Nurindah; Suhita, Raheni; Wijayanti, Kenfitria Diah (Universitas Sebelas Maret, 2020)
This research is included in descriptive quality research using content analysis method, aimed to describing some points in Javanese news text written by students: (1) form of ineffective sentence in Javanese news text written by students; (2) factor causing ineffective sentence in Javanese news text written by students; and (3) effort that could be done to overcome the ineffective sentence in Javanese news text written by students. The effective sentence can be seen based from five characteristics: (a) comparability and unity; (b) parallels; (c) emphasis; (d) frugality; and (e) variety. Noting these, there are 92 ineffective sentence forms were found in Javanese news text written by students. The factors who causing ineffective sentence in Javanese news text written by students included: (a) lack of Javanese vocabulary owned by students; (b) lack of references; (c) lack of motivation from student; and (d) lack of insight into effective sentences and their rules. The last, some efforts to overcome the ineffective sentence in Javanese news text written by students: (a) increase the scope of vocabulary owned by student; (b) add references; (c) increase student motivation; and (d) broadening student’s insight about effective sentence and their rules.